Problem:
"(x^2+1)\\times \\dfrac{\\partial^2 y}{\\partial x^2}+x\\times \\dfrac{\\partial y}{\\partial x}-y=0" (1)
Let's image solution of the task in the next view:
"y=x^\\sigma(a_{0}+a_{1}x+a_{2}x^2+...a_{k}x^k+...)" (2)
Now subsitute equation (2) into equation (1):
"(x^2+1)\\times(\\sigma\\times(\\sigma-1)\\times a_{0}x^{\\sigma-2}+(\\sigma+1)\\times\\sigma\\times a_{1}x^{\\sigma-1}+(\\sigma+2)\\times(\\sigma+1)\\times a_{2}x^{\\sigma}+...)+x\\times(\\sigma\\times a_{0}x^{\\sigma-1}+(\\sigma+1)\\times a_{1}x^{\\sigma}+(\\sigma+2)\\times a_{2}x^{\\sigma+1}+...)-(a_{0}x^{\\sigma}+a_{1}x^{\\sigma+1}+a_{2}x^{\\sigma+2}+...)=0"
Or:
"\\sigma\\times(\\sigma-1)\\times a_{0}x^{\\sigma-2}\n+ (\\sigma+1)\\times\\sigma\\times a_{1}x^{\\sigma-1} + \n(\\sigma\\times(\\sigma-1)\\times a_{0}+(\\sigma+2)\\times(\\sigma+1)\\times a_{2}+\\sigma\\times a_{0}-a_{0})x^{\\sigma}+...=0"
Now equate all coefficient near "x^{\\sigma-2}" , "x^{\\sigma-1}", "x^{\\sigma}",... to zero:
"\\begin{cases}\na_{0}\\times(\\sigma-1)\\times\\sigma=0 \\\\\na_{1}\\times(\\sigma+1)\\times\\sigma=0 \\\\\na_{0}\\times(\\sigma+1)\\times(\\sigma-1)-a_{2}\\times(\\sigma+2)\\times(\\sigma+1)=0 \\\\\na_{1}\\times\\sigma\\times(\\sigma+2)-a_{3}\\times(\\sigma+3)\\times(\\sigma+2)=0\\\\\n.... \\\\\na_{k}\\times(\\sigma-k+1)\\times(\\sigma+k+1)-a_{k+2}\\times(\\sigma+k+2)\\times(\\sigma+k+1)=0\\\\\n\\end{cases}" (3)
From the first equation (using that "a_{0}\\not=0") we get:
"\\sigma=0" or "\\sigma=1"
Case: "\\sigma=1"
Our system (3) will have the next view:
"\\begin{cases}\n0=0\\\\\na_{1}\\times 2=0\\\\\na_{0}\\times 0-a_{2}\\times 3=0\\\\\na_{1}\\times 3-a_{3}\\times12=0\\\\\n...\n\\end{cases}"
Or:
"\\begin{cases}\n0=0\\\\\na_{1}=0\\\\\na_{2}=0\\\\\na_{3}=0\\\\\n...\\\\\n\\end{cases}"
So we have that all coefficient "a_{k}" (except "a_{0}") are equal zero. So solution of this problem in this case is:
"y=a_{0}\\times x^{\\sigma}",
But for this case "\\sigma=1", so
"y=a_{0}\\times x", where "a_{0}" is a different constant.
Case: "\\sigma=0"
Our system (3) will have the next view:
"\\begin{cases}\n0=0\\\\\n0=0\\\\\n-a_{0}-2\\times a_{2}=0\\\\\na_{1}\\times 0 - a_{3}\\times 6=0\\\\\n...\n\\end{cases}"
Or:
"\\begin{cases}\na_{2}=-\\dfrac{a_{0}}{2}\\\\\na_{3}=0\\\\\n...\n\\end{cases}"
So we have that coefficient "a_{3}", "a_{5}", ... are equals to zero, and the pairs coefficient(and "a_{1}") aren't equal to zero. For convenience let's get: "a_{1}=0".
For this case, the genral solution will have the next view:
"y=a_{0}+a_{2} x^2+ a_{4}x^4+...=\n\\begin{matrix}\n \\\\\n\\sum \\\\\n_{k=0}\n\\end{matrix}\na_{2k}x^{2k}"
Comments
Leave a comment